2017
DOI: 10.3390/su9030411
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Middle East Respiratory Syndrome Outbreak on Online and Offline Markets for Retail Sales

Abstract: This study investigates whether the Middle East Respiratory Syndrome (MERS) outbreak in Korea affected online and offline retail sales and determines the presence of a substitution or delay effect between the two. We analyze the monthly retail sales of electronic goods, semi-luxury goods, and groceries using an autoregressive integrated moving average (ARIMA) model with intervention. The findings are as follows. First, offline sales of electronic goods declined by 7.9%, while online sales increased by 7.03%, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 61 publications
(108 reference statements)
1
25
0
Order By: Relevance
“…As far as the impact on tourism from MERS is concerned, after the outbreak period was over, namely January to June 2016, the projected values for tourism (namely the ones adapted for the damage the virus had inflicted on tourism) were not much different from the real ones. The fact that this virus outbreak had lighter effects on the economy is also suggested in Jung and Sung (2017) who found that groceries sector received no negative impact, offline sales of electronics declined by 7.9% and online sales increased by 7.03% indicating that these two markets behaved as substitutes. Last, according to the same study semi-luxury goods demand decreased for two months only.…”
Section: Mers-cov: Middle East Respiratory Syndrome (2015)mentioning
confidence: 71%
See 1 more Smart Citation
“…As far as the impact on tourism from MERS is concerned, after the outbreak period was over, namely January to June 2016, the projected values for tourism (namely the ones adapted for the damage the virus had inflicted on tourism) were not much different from the real ones. The fact that this virus outbreak had lighter effects on the economy is also suggested in Jung and Sung (2017) who found that groceries sector received no negative impact, offline sales of electronics declined by 7.9% and online sales increased by 7.03% indicating that these two markets behaved as substitutes. Last, according to the same study semi-luxury goods demand decreased for two months only.…”
Section: Mers-cov: Middle East Respiratory Syndrome (2015)mentioning
confidence: 71%
“…Based on World Bank estimations, SARS has cost to the global economy about $54 billion, while a flu pandemic would cost $ 3 trillion, namely 5% of global GDP. The SARS is supposed to have affected most negatively tourism (-64.31%), worse than the Asian financial crisis of 1997 (-2.54%), September 11 th attack (-24.59%), Taiwan earthquake in 2001 (-17.07%) based on claims by Jung and Sung (2017). Siu and Wong (2004) found that the impact of SARS was noted on demand rather than the supply of the economy.…”
Section: Sars: Severe Acute Respiratory Syndrome (2003)mentioning
confidence: 99%
“…However, previous studies on the impact of MERS on the tourism industry were not conclusive because most studies employed a SARIMA model (Song, 2016), ARIMA model (Sung, 2016), or SVAR (Suh & Kim, 2018). The methods can be limited to calculate the specific effect sizes for MERS (Jung & Sung, 2017). As such, to resolve these issues, this research provides more integrated methodologies focused on the impact of MERS on Korea's inbound tourism demands employing a variety of rigorous forecasting methods (i.e., ARIMA, Winters Exponential Smoothing, Stepwise Autoregressive Model).…”
Section: Mers Outbreak and Its Impact On Koreamentioning
confidence: 99%
“…Fatal epidemics have scared people because of unknown preventions and cures, which has, in turn, influenced tourism. Specifically, the spread of epidemics is closely related to living in a globalized world, not only limits individual's activities, but also results in a country's economic loss (Jung & Sung, 2017). Prior research has dedicated sensitive economic sectors such as inbound tourism, hotel, and airlines.…”
Section: Tourism and Epidemicsmentioning
confidence: 99%
“…In a study conducted by Jung and Sung (2017), the researchers concluded that people often change their economic behavior in response to an unexpected situation. The majority of the previous researches identified a decline in retail sales and in economic growth at a macro-level or at a sectorial level due to unconscious responses in people based on their dread of contracting the infection from any outdoor activity.…”
Section: Literature Reviewmentioning
confidence: 99%